Estudo das características e da viabilidade do uso de resíduos gerados no polimento de rochas graníticas como adição em concretos - Moises Silva Alves (2008)
Brazil is one of the great producers of ornamental rocks in the world-wide market. These rocks are widely used in the construction business. Its use has been growing year after year. So has the wastes as its process take place. Brazil creates yearly, about 280,000 m³ of waste, only by shaping and burnishing granites. Recycling contributes for the reduction of not renewable raw material consumption for the reduction of degraded areas for the extraction of these raw materials and even for the reduction of wastes final disposal areas. The mineral additions are considered material suplemental added to cements or concrete. Using mineral additions has proportionate mechanical improvement properties and durability of the concretes. This goal work is studying the waste features and to evaluate its use as mineral addition in concrete. The study tries to evaluate the application of the granite waste in its original form. Without milling, searching for a cheaper option at its application of economic form. This work involves the characterization of the waste and of the components used in concrete, the pozzolanic activity study and waste filler effect. Also involves the determination of concrete materials proportion, and the evaluation of mineral additions influence in concrete properties. The pozzolanicity tests were made by physical and chemical methods. They had shown that the studied waste does not present pozzolanic activity. Despite the waste shows in its chemical composition, the sum of SiO2, Al2O3, and Fe2O3 higher then 50%, this material has crystal structure. This fact compromises the pozzolanic activity development. In general, the concretes, in addition of the granite waste, had shown porosity and permeability reduction, providing properties improvement en its hard form compared to the reference ones. This improvement certainly is related to this addition filler effect.